Shopaholic to the star - Kinsella, Sophie (Black Swan, 2014)
Becky Brandon (nee Bloomwood) is in Hollywood ! Its as if all her life has been leading to this moment. Shes hanging out with the stars. Or at least she will be, when she finally gets to meet movie superstar Sage Seymour, whom husband Luke is now managing. Theres so much to see and do! And getting Minnie through the hurdles for her A-list Hollywood pre-school will require some her help. Becky sets her heart on a new career - shes going to be a celebrity stylist. Red carpet, here she comes! But Becky soon finds its tough in Tinseltown. Luckily her best friend Suze comes over to keep her company, and together they embark on the Hollywood insider trail But somehow ...things arent quite working out as theyd hoped. Then Beckys big chance comes, and its an opportunity that money cant buy. But will it cost her too much?